The Effect of Pulping Process Variable and Elemental Chlorine Free Bleaching on the Quality of Oil Palm Trunk Pulp - Wieke Pratiwi; Andoyo Sugiharto; Susi Sugesty (JURNAL SELULOSA, 2018)
Oil Palm Trunk (OPT) is a non-wood cellulosic raw material which is not yet widely utilized in pulping and papermaking. Research on the utilization of abundant Oil Palm Trunk (OPT) from Sabah (Malaysia) and Lebak (West Java Province) for pulp production was carried out using kraft and soda anthraquinone processes with active alkali (AA) of 13-17%. The raw material was chipped and depithed as pretreatment. Bleaching of pulp was carried out using Elemental Chlorine Free (ECF) process. Analysis of raw material covered physical and chemical properties, and fiber morphology. Both OPT fibers were classified into the moderate fiber length (1.05-1.37 mm). Sabah OPT were very bulky with the chips pile density of 102.16 kg/m3 and 62.91 kg/m3 for undepithed and depithed OPT, respectively. The physical properties of OPT pulps were comparable to that of Acacia mangium pulp. With respect to the bleachability and physical properties, pulping of Lebak OPT using kraft or soda-anthraquinone process with AA of 15% were considered as optimum condition. Depithing on Sabah OPT with high pith content could increase physical properties of pulp. ODEoDnD bleaching sequence on pulps from Sabah OPT gave satisfactory results with respect to the physical properties. Since Sabah OPT had a high pith content, the yields of bleached pulp were relatively low (24.67-26.73%). However, the physical properties of the undepithed and depithed Sabah OPT bleached pulp were higher compared to those of the SNI of Leaf Bleached Kraft Pulp (LBKP).Keywords: depithing, Elemental Chlorine Free, bleached pulp, physical properties, LBKP Pengaruh Variabel Proses Pulping dan Pemutihan Elemental Chlorine Free pada Kualitas Pulp Batang Kelapa SawitAbstrakBatang Kelapa Sawit adalah bahan baku selulosa non-kayu yang belum banyak digunakan dalam pembuatan pulp dan kertas. Penelitian tentang pemanfaatan Batang Kelapa Sawit (BKS) dari Sabah (Malaysia) dan Lebak (Provinsi Jawa Barat) yang berlimpah untuk produksi pulp menggunakan proses kraft dan soda antrakuinon dengan alkali aktif (AA) kisaran 13-17% telah dilakukan. Penyerpihan dan proses depithing bahan baku dilakukan sebagai perlakuan awal. Pemutihan pulp dilakukan menggunakan Elemental Chlorine Free (ECF). Analisis bahan baku mencakup sifat fisik dan kimia, serta morfologi serat. Kedua serat BKS dapat diklasifikasikan sebagai serat moderat dengan panjang 1,05-1,37 mm. BKS dari Sabah sangat ruah dengan densitas tumpukan serpih masing-masing 102,16 kg/m3 untuk yang belum di-depithing dan 62,91 kg/m3 untuk yang telah di-depithing. Sifat fisik pulp BKS sebanding dengan pulp dari Acacia mangium. Sehubungan dengan kemampuan pemutihan dan sifat fisik, pembuatan pulp BKS dari Lebak menggunakan proses kraft atau soda-antrakuinon dengan AA 15% adalah kondisi optimal. Depitihing BKS dari Sabah dengan kandungan pith yang tinggi dapat meningkatkan sifat fisik pulp. Pemutihan dengan urutan ODEoDnD untuk pulp BKS dari Sabah memberikan hasil sifat fisik yang memuaskan. BKS dari Sabah memiliki kandungan pith yang tinggi sehingga rendemen pulp yang diputihkan relatif rendah (24,67-26,73%). Namun, sifat-sifat fisik pulp putih BKS dari Sabah yang belum dan telah di-depithing lebih tinggi dibandingkan SNI Pulp Kraft Putih Kayudaun (LBKP).Kata kunci: depithing, Elemental Chlorine Free, pulp putih, sifat fisik, LBKP